2013
DOI: 10.1371/journal.pone.0061508
|View full text |Cite|
|
Sign up to set email alerts
|

Divergent Roles of Amino Acid Residues Inside and Outside the BB Loop Affect Human Toll-Like Receptor (TLR)2/2, TLR2/1 and TLR2/6 Responsiveness

Abstract: TLR2 specifically recognizes a wide range of ligands by homodimerizing or heterodimerizing with TLR1 or TLR6. However, the molecular basis of the specific signalling transduction induced by TLR2 homodimerization or heterodimerization with TLR1 or TLR6 is largely unknown. In this study, we found three amino acid residues, two (663L and 688N) outside and one (681P) inside the BB loop, which were conserved in all of the TLRs, except for the TLR3 toll/IL-1R(TIR) domain. The responsiveness of human TLR2/2, TLR2/1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Our results show that both TLR2/1 and TLR2/6 yielded an inhibitory effect on SERT by triggering the same mechanism. These results may suggest a redundant effect of TLR2 in intestinal epithelial cells; this feature of TLR2 has also been found in other cell types [48], although recent results have concluded that TLR2/1 and TLR2/6 could exhibit specific signaling transduction [49]. In relation to the ability shown by TLR2 to inhibit SERT activity and expression by different pathways depending on the period of treatment, it might be considered an advantageous way of specialization to modulate 5-HT in different situations.…”
Section: Discussionmentioning
confidence: 90%
“…Our results show that both TLR2/1 and TLR2/6 yielded an inhibitory effect on SERT by triggering the same mechanism. These results may suggest a redundant effect of TLR2 in intestinal epithelial cells; this feature of TLR2 has also been found in other cell types [48], although recent results have concluded that TLR2/1 and TLR2/6 could exhibit specific signaling transduction [49]. In relation to the ability shown by TLR2 to inhibit SERT activity and expression by different pathways depending on the period of treatment, it might be considered an advantageous way of specialization to modulate 5-HT in different situations.…”
Section: Discussionmentioning
confidence: 90%
“…Here, we report a novel method of TIR domain alignment of MyD88-dependent pathwaymediated TLRs with MyD88-independent pathway-mediated TLR3 to identify essential residues in the TLR4 signaling pathway. This approach is simple and informative and was successful in the identification of three critical amino acids in TLR2 signaling [18]. Although both L696 and P714 were demonstrated in a previous study to be essential for TLR4 signaling using systemically alanine replacement [17], our approach also revealed an additional critical residue: N721.…”
Section: Discussionmentioning
confidence: 81%
“…However, in the P681H mutant, additional interactions are formed with residues from the αC helix (Supporting Information, Figure S11F). Residues 713C, 748R, 749F,752L, and 753R were identified to be crucial for TLR1‐TLR2 signaling using alanine‐scanning mutagenesis . Among these, 752L, 749F, and 712W are few residues mediating the network of interactions in Community 2.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of Tyr 761 in the TIR domain of TLR2 is essential for its proper functioning . TLR2‐mediated signaling has been well‐studied and ample experimental information is known, including the effect of various mutations in its TIR domain on its function …”
Section: Introductionmentioning
confidence: 99%